1976
DOI: 10.1159/000275264
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthine Anomalies in Trisomy 13 Mosaicism

Abstract: The temporal bone histopathology of a 2-month-old male with a bilateral cleft palate, cleft lip and polydactylia due to trisomy 13 mosaicism was studied. Anomalies in the ear involved a partial absence of the superior semicircular canal, an abnormally wide lateral semicircular canal, underdeveloped cochlear coils, an abnormally broad modiolus, an undeveloped organ of Corti and an underdeveloped basilar membrane in the basal turn of the cochlea, an unusually wide cochlear aqueduct, and deformed stapedial crura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The patient ages ranged from birth to 40 years for females and birth to 38 years for males. One miscarriage [Sperber and Honoré, 1988], two elective abortions [Eubanks et al, 1998; Halder et al, 2005], and nine deaths in the first 4 months of life were reported [Patient 2; Bain et al, 1965 (two cases); Wilson and Melnyk, 1967; Taylor et al, 1970; Schinzel et al, 1974; Suga et al, 1976; Lorch et al, 1978; Hsu and Hou, 2007]. Unfortunately, little information regarding the cause of death in infancy was given in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…The patient ages ranged from birth to 40 years for females and birth to 38 years for males. One miscarriage [Sperber and Honoré, 1988], two elective abortions [Eubanks et al, 1998; Halder et al, 2005], and nine deaths in the first 4 months of life were reported [Patient 2; Bain et al, 1965 (two cases); Wilson and Melnyk, 1967; Taylor et al, 1970; Schinzel et al, 1974; Suga et al, 1976; Lorch et al, 1978; Hsu and Hou, 2007]. Unfortunately, little information regarding the cause of death in infancy was given in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…In 1976, Suga et al (2) presented the first evidence of ECA from the temporal bone histopathology of a 2-month-old boy with Trisomy 13. It was not until two decades later, however, when Fatterpekar et al (3) published data on normal cochlear aperture dimensions, that research into ECA progressed.…”
mentioning
confidence: 99%